2006
DOI: 10.1016/j.devcel.2006.03.010
|View full text |Cite
|
Sign up to set email alerts
|

PP2A Is Required for Centromeric Localization of Sgo1 and Proper Chromosome Segregation

Abstract: Loss of sister-chromatid cohesion triggers chromosome segregation in mitosis and occurs through two mechanisms in vertebrate cells: (1) phosphorylation and removal of cohesin from chromosome arms by mitotic kinases, including Plk1, during prophase, and (2) cleavage of centromeric cohesin by separase at the metaphase-anaphase transition. Bub1 and the MEI-S332/Shugoshin (Sgo1) family of proteins protect centromeric cohesin from mitotic kinases during prophase. We show that human Sgo1 binds to protein phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
349
4
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(373 citation statements)
references
References 39 publications
15
349
4
5
Order By: Relevance
“…The role of Sgo in the regulation of mitotic cohesion has been addressed in a number of recent studies, mainly in yeast and human cells McGuinness et al 2005;Vaur et al 2005;Kitajima et al 2006;Tang et al 2006;Kawashima et al 2007;Vanoosthuyse et al 2007;Lee et al 2008). However, this is the first time that the Xenopus egg cell free system, in which vertebrate cohesin was initially characterized, is used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of Sgo in the regulation of mitotic cohesion has been addressed in a number of recent studies, mainly in yeast and human cells McGuinness et al 2005;Vaur et al 2005;Kitajima et al 2006;Tang et al 2006;Kawashima et al 2007;Vanoosthuyse et al 2007;Lee et al 2008). However, this is the first time that the Xenopus egg cell free system, in which vertebrate cohesin was initially characterized, is used.…”
Section: Discussionmentioning
confidence: 99%
“…Anomalous PP2A distribution in the absence of Sgo impairs cohesin release Sgo associates with PP2A in yeast and human cells, and this association is important for cohesin protection (Kitajima et al 2006;Riedel et al 2006;Tang et al 2006). In HeLa cells depleted of Sgo1 by siRNA, cohesion is completely lost even though the centromeric localization of PP2A is preserved, a result that led Kitajima et al (2006) to suggest that Sgo could have an additional role and provide protection by itself, maybe through physical association with cohesin.…”
Section: Cohesin Distribution Is Affected By Sgo Depletionmentioning
confidence: 99%
“…Therefore, it is critical for cells to guard centromeric cohesion from the actions of mitotic kinases before the onset of anaphase. Recently, PP2A has been shown to associate with Shugosin (Sgo1; Drosophila, MEI-S332), one of the proteins that is needed for the protection of centromeric cohesion in animals (32,33). In addition, the association of PP2A with Sgo1 has been shown to be necessary for the centromeric localization of Sgo1 and proper chromosome segregation in human cells (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, PP2A has been shown to associate with Shugosin (Sgo1; Drosophila, MEI-S332), one of the proteins that is needed for the protection of centromeric cohesion in animals (32,33). In addition, the association of PP2A with Sgo1 has been shown to be necessary for the centromeric localization of Sgo1 and proper chromosome segregation in human cells (32,33). The data shown here are consistent with the role of PP2A in the protection of chromosome segregation, for cantharidin treatment of mitotic cells at concentrations that inhibit the activity of PP2A results in the dissociation of the chromosomes aligned on the metaphase plate in a random and unorganized manner.…”
Section: Discussionmentioning
confidence: 99%
“…1), to protect the centromeric cohesion in mitosis, thus preventing chromosome missegregation and chromosome instability. [16][17][18][19][20] Our recent immunofluorescence microscopy demonstrated that Sgo1 is sequentially recruited to kinetochores and inner centromeres. 10 The kinetochore and centromeric receptors for Sgo1 are histone H2A phosphor Thr120 (H2A pT120) and cohesin, respectively.…”
mentioning
confidence: 95%